Maritime Human Resources Performance Analysis Case Studies of Ship's Crewers - Hendrawan, Andi; Hendrawan, Aji Kusumastuti; Pramomo, Sri; Lusiani, Lusiani (Saintara : Jurnal Ilmiah Ilmu-Ilmu Maritim, 2024)
Different from work on land which is far from waves and storms, at sea climate and weather changes can occur at any time. If previously the weather was sunny, a few minutes later the weather could turn dark. Because the work is so hard, good performance is needed so that everything is fine. The research examined the crew of the Elbidu ship, totaling 30 people, using a survey approach. The results show that the performance of the crew both as a team and individually is good because the crew always maintains unity and increases their competence.